2018
DOI: 10.12968/hmed.2018.79.11.643
|View full text |Cite
|
Sign up to set email alerts
|

Assessing antibiotic stewardship using the surgical site infection prevention bundle

Abstract: Background: Antibiotic prophylaxis is crucial in head and neck surgery to prevent infection from clean contaminated wounds. Scottish Intercollegiate Guidelines Network (SIGN) guidance, the gold standard of practice, recommends that administration of broad spectrum antibiotics is discontinued after 24 hours post-operation. A three-audit cycle quality improvement project was conducted to assess clinical practice against SIGN guidance at a large London teaching hospital. Methods: Three change initiatives were imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies evaluated the use of indication or reason for use; however, there were six studies that described the use of accountable justification (ie, where a rationale is required for potentially inappropriate prescribing such as antibiotics for upper respiratory tract infection),45 48 50 85 87 99 and two that used both indication and justification 98 119…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other studies have also used Microguide to identify specific antibiotic protocols for other conditions, clearly showing it to be a popular resource. [3][4][5] Antimicrobial stewardship is one of the key pillars of the UK's five-year strategy to prevent antimicrobial resistance. 1 It has been shown that many initial antimicrobial prescriptions on admission are unchanged, and thus it is essential that the appropriate antimicrobial(s) are prescribed at hospital attendance.…”
Section: Discussionmentioning
confidence: 99%
“…After screening, six of these papers related specifically to the Microguide antimicrobial application. [1][2][3][4][5][6] To our knowledge, there has been no previous review of the recommendations for ENT conditions included on Microguide across different NHS trusts. Our aim was to review the ENT-related conditions listed for each NHS hospital on the Microguide application.…”
Section: Introductionmentioning
confidence: 99%